Towers in the city Berlin Alexanderplatz - Kollhoff, Hans 1946- (Yale School of Architecture, 2021)
"This book examines the tower as the architectural expression of a long-term commitment to the city, arguing that development must be driven not only by property value and architectural ingenuity but also by a responsibility to collective memory and to a common humanity. These public commitments find architectural expression in a tectonic radically different to that of contemporary patterns of development. Taking Berlin's Alexanderplatz as an opportunity for studying the role of the skyscraper within the urban fabric, the volume presents a series of prompts, provocations, and projects to address the challenge of designing a tower that can be understood as a monolithic whole, even if it is assembled from discrete parts" -- Amazon.com
Includes bibliographical references
Keywords: Hochhaus; Entwurf; Alexanderplatz -- Berlin; Tall buildings / Germany / Berlin; Skyscrapers / Germany / Berlin; Architecture / Study and teaching; Alexanderplatz (Berlin, Germany); Architecture; Study and teaching; Skyscrapers; Tall buildings; Germany; Berlin; Germany; Berlin; Alexanderplatz; Germany / Berlin; Germany / Berlin / Alexanderplatz